Motivation, resources and the organization of the school system - Albornoz, Facundo; Berlinski, Samuel; Cabrales, Antonio (Wiley, 2017)
This paper studies a model where student effort and talent interact with parental and teachers' investments, as well as with school system resources. The model is rich, yet sufficiently stylized to provide novel implications. It can show, for example, that an improvement in parental outside options will reduce parental and school effort, which are partially compensated through school resources. In this way, by incorporating the behavioral responses of parents, teachers and policymakers, the paper provides a rationale for the existing ambiguous empirical evidence on the effect of school resources. The paper also provides a novel microfoundation for peer effects, with empirical implications for welfare and different education policies.